Pembuatan Nomor Induk Berusaha (NIB) Melalui Web Online Single Submission (OSS) untuk UMKM di Kelurahan Tlumpu - Natasye Wulan Meilina Rini; Daisy Marthina Rosyanti; Ayunda Evanthi; Khoirul Anam; Muhammad Rafli; Adinda Eka Novita Sari (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Business perpetrators specifically the perpetrators of Small and Medium Enterprise in Tlumpu village of Blitar city is through growing phase every year. On this growing, business needed some permits to get some legality and protection from the goverment. However, the prepetrators in Tlumpu village still don’t know and still lack knowledge about how to get Business Identification Number (NIB) via Online Single Submission’s web (OSS). The aim of community service activities is to clear the problem about business legality in Tlumpu village, where is this activity helped to introduce, increase knowledge, and assist the perpetrators business in Tlumpu village to make Business Identification Number (NIB). The implementation method used in this activity includes 3 stages namely socialization, training, and mentoring. The implementation of activities includes the delivery of theory, assistance in making NIB business licenses, and submission of NIB certificates to the perpetrators of business in Tlumpu Village. The result of this activity is the business perpetrators knowing the importance of legality in business and the registration of businesses into the OSS institution, thus the perpetrators of Small and Medium Enterprise in Tlumpu Village get business protection, ease of access to capital, and empowerment from the government, as well as assistance in the development of Small and Medium Enterprise